Thrips biological control agent shows greater niche overlap with invasive alligatorweed than conventional agent in current and future climate scenarios - Samuel A. Schmid; Andrés F. Sánchez-Restrepo; Alejandro J. Sosa; Gray Turnage; Gary N. Ervin (BioControl, 2025)

Submersed herbicides and thrips biological control effectively reduce biomass of alligatorweed (Alternanthera philoxeroides), a widespread aquatic invasive plant - Samuel A. Schmid; Gray Turnage; Gary N. Ervin (BioControl, 2024)

Recent post-release evaluations of weed biocontrol programmes in South Africa: a summary of what has been achieved and what can be improved - Iain D. Paterson; Samuel N. Motitsoe; Julie A. Coetzee; Martin P. Hill (BioControl, 2024)
Biocontrol is widely considered an effective management solution for mitigating the negative impacts of invasive alien plants (weeds). Globally, post-release evaluations to assess individual biocontrol programmes are generally lacking and there have been persistent calls within the biocontrol of weeds literature to increase the quantity and quality of post-release evaluation studies. South African biocontrol researchers have prioritised post-release evaluation studies, with a significant proportion of funding dedicated to this purpose. In this study we review post-release evaluations of weed biocontrol programmes in South Africa that have been published in the last ten years, discuss the different ways these evaluations have been conducted, and identify gaps for future research. Post-release evaluations have been conducted at different scales, including physiological changes within individual plants, plant growth parameters, plant population dynamics and landscape level changes. In most cases, the results of these studies indicated that biocontrol has reduced invasions according to these metrics. While the reduction in the invasion is assumed to alleviate negative ecological and socio-economic impacts, this is usually not directly measured. Evaluations of the socio-economic and ecosystem level benefits of biocontrol were limited to just a few examples on aquatic weeds. More studies that investigate the landscape, socio-economic and ecosystem level changes due to biocontrol are required, especially for terrestrial weeds, if the true scale of the benefits provided by biocontrol are to be understood.

Efficacy of a mirid predator and an eulophid parasitoid to the tomato potato psyllid Bactericera cockerelli control on pepper plants - Alejandro O. Guzmán-Pedraza; Ana Mabel Martínez; Ángel Rebollar-Alviter; Luis J. Palma-Castillo; Sinue I. Morales-Alonso; Juan M. Chavarrieta-Yáñez; José I. Figueroa; Samuel Pineda (BioControl, 2024)

Physiological host range of Trissolcus japonicus in relation to Halyomorpha halys and other pentatomids from California - Jesús R. Lara; Charles H. Pickett; Matthew T. Kamiyama; Samuel Figueroa; Mariana Romo; Christopher Cabanas; Vanessa Bazurto; Vincent Strode; Kristen Briseno; Mike Lewis; Joshua Oliva; Gabriel Hernandez; et al. (BioControl, 2019)

Pre-planting inoculation for early establishment of Dicyphus bolivari and D. errans on tomatoes - Filipe Madeira; Eva Edo; Samuel Sossai; Joan Callizo; Ramon Albajes (BioControl, 2019)

The influence of temperature on the flight capacity of emerald ash borer Agrilus planipennis and its parasitoid, Tetrastichus planipennisi: implications to biological control - Samuel J. Fahrner; Jonathan P. Lelito; Brian H. Aukema (BioControl, 2015)

Pollen on-twine for food provisioning and oviposition of predatory mites in protected crops - Einat Adar; Moshe Inbar; Shira Gal; Samuel Gan-Mor; Eric Palevsky (BioControl, 2014)

Stabilisation of heat tolerance traits in Heterorhabditis bacteriophora through selective breeding and creation of inbred lines in liquid culture - Samuel Anbesse; Nanette Hope Sumaya; Anna Verena Dörfler; Olaf Strauch; Ralf-Udo Ehlers (BioControl, 2013)

Studies on the fungi associated with the glassy-winged sharpshooter Homalodisca coagulata with emphasis on a new species Hirsutella homalodiscae nom. prov. - Drion Garth Boucias; Dansia W. Scharf; Samuel E. Breaux; Dusty H. Purcell; Russell E. Mizell (BioControl, 2007)